THE ANALYSIS OF CURRENT MEASURES AND REFORMS IN ENSURING THE FOUR DIMENSIONS OF FOOD SECURITY IN PEOPLE’S REPUBLIC OF CHINA - Zhang Hui (EPRA International Journal of Economic Growth and Environmental Issues(EGEI), 2023)
Food security is a global concern, and the People's Republic of China, with its massive population and diverse landscapes, faces unique challenges in ensuring the availability, accessibility, utilization, and stability of food. This article presents a qualitative analysis of the current measures and reforms in place to address these four dimensions of food security in China. The research draws on document analysis of government reports, policy documents, and academic research papers, along with semi-structured interviews with key informants, including government officials, policymakers, scholars, and experts in the field of food security. By employing a qualitative methodology, the study provides a comprehensive understanding of China's multifaceted approach to food security. The findings reveal significant progress in addressing food security dimensions and highlight the complexity of ensuring food security in a rapidly evolving nation. The research contributes to the global dialogue on food security and offers valuable insights into China's experiences that can inform policy and research in other regions.